2015
DOI: 10.3109/07380577.2015.1116129
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity of the International Family Quality of Life Survey

Abstract: The measurement of the social construct of Family Quality of Life (FQOL) is a parsimonious alternative to the current approach of measuring familial outcomes using a battery of tools related to individual-level outcomes. The purpose of this study was to examine the internal consistency and concurrent validity of the International FQOL Survey (FQOLS-2006), using cross-sectional data collected from 65 family caregivers of children with developmental disabilities. It shows a moderate correlation between the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…The family involvement in turn fosters greater parental responsibility, improves family skills, and generates a higher level of satisfaction in the family [ 14 ]. Moreover, as Samuel et al, argue, “families that function well support societies and families with an effective quality of life are a social resource.” [ 15 ] (p. 188). These are all solid reasons that support the adoption of this family model in EC, a model that has the family as a core dimension and whose ultimate goal is to promote a better quality of family life.…”
Section: Introductionmentioning
confidence: 99%
“…The family involvement in turn fosters greater parental responsibility, improves family skills, and generates a higher level of satisfaction in the family [ 14 ]. Moreover, as Samuel et al, argue, “families that function well support societies and families with an effective quality of life are a social resource.” [ 15 ] (p. 188). These are all solid reasons that support the adoption of this family model in EC, a model that has the family as a core dimension and whose ultimate goal is to promote a better quality of family life.…”
Section: Introductionmentioning
confidence: 99%
“…Even though-as pointed out-numerous papers have in recent years have focused on the construction, validation, or study of tools to measure FQoL [14,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], authors agree on the need to continue to devote efforts to optimizing their internal structures and revising how they work in different populations in different contexts (socio-demographic, cultural, etc.) [25,29,31,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The final section of the survey includes items about overall impressions of FQOL [ 30 ]. The survey had good reliability and validity for caregivers of people with DD [ 31 33 ]. Using data from Australia, Canada, and the United States, it was reported that the four indicators ( Initiative , Opportunities , Attainment , and Satisfaction), and the nine-domain factor structure of the FQOLS-2006 had an acceptable level of construct validity [ χ 2 (27) = 55.32, p < 0.00, CFI = 0.93, AGFI = 0.94 RMSEA = 0.06] [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent validity showed moderate correlations between five FQOLS-2006 domains and conceptually related domains. Cronbach's alpha internal consistency of the nine domains ranged from poor to good (0.43 to 0.83) and, for the two-item global FQOL, it was 0.85 [ 33 ].…”
Section: Introductionmentioning
confidence: 99%